Platinum-doped carbon nanoparticles inhibit cancer cell migration under mild laser irradiation: Multi-organelle-targeted photothermal therapy. (November 2018) - Bao, Yan-Wen; Hua, Xian-Wu; Chen, Xiaokai; Wu, Fu-Gen
Abstract: Tumor growth and metastasis are two main causes of cancer-related deaths. Here, we simultaneously investigated the effects of nanoparticles on cancer cell viability and migration using polyethylene glycol (PEG)-modified, platinum-doped (<4 mol %) carbon nanoparticles (denoted as PEG-PtCNPs). The bare PtCNPs were prepared by the facile one-step hydrothermal treatment of p -phenylenediamine and K2 PtCl4 in aqueous solution. After PEGylation, the obtained PEG-PtCNPs can serve as an excellent photothermal nanoagent for cell migration inhibition, laser-triggered nuclear delivery, effective tumor accumulation, and imaging-guided tumor ablation with improved therapeutic efficacy and reduced side effects. In the absence of laser exposure, the positively charged PEG-PtCNPs with a hydrodynamic diameter of ∼19 nm easily entered the cells by endocytosis and were located in multiple organelles (including mitochondrion, endoplasmic reticulum, lysosome, and Golgi apparatus), causing a slight increase in the expression level of nuclear protein lamin A/C. Upon mild laser irradiation (0.3 W cm −2 ), the fragmented cytoskeletal structures and overexpression of lamin A/C were observed, thus inhibiting cancer cell migration. Furthermore, hyperthermia induced by PEG-PtCNPs plus laser irradiation at a higher power density (1.0 W cm −2 ) could cause irreversible damage to the nuclear membranes and then facilitate the nuclear delivery of the nanoagents without the introduction of nuclear targeting ligands. Taken together, this work develops a facile synthetic approach of platinum-based carbon nanoparticles with excellent photothermal properties, and demonstrates their potential applications for modulating tumor metastasis and realizing multi-organelle-targeted tumor ablation. Graphical abstract: Image 1